F.M. Dostoevsky’s Lawyers: from the History of the “Kumanin Process” - Yulia V. Yukhnovich (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article is dedicated to the relations between Dostoevsky and the lawyers that influenced his valuation of the judicial reforms in 1860–1870s, and to the difficult lawsuit about the Kumanin’s heritage, in which the writer was involved in the same years. Dostoevsky’s memoirs and correspondence with the brother Andrey Mikhailovich shows how lawyers fraudulently profited from their guarantors. Some letters from Dostoevsky’s lawyers also contain information that concedes to suspect them of deliberate obfuscation of the case. The intrigues of lawyers negatively affected the relationship of the writer with his sisters, who expected to receive part of the inheritance according to the will and accused the brother of intending to contest their rights. Legal proceedings and disputes between relatives led to the sad outcome of the “Kumanin heritage case”, as a result of which none of its participants was able to get a legal part of the “fatal” inheritance.